Sosialisasi Pengelolaan Limbah Plastik Menjadi Eco Paving (di RT. 33 RW. 04 Kel. Pematang Gubernur Kota Bengkulu) - Putri, Tiara Renita; Oktafiani, Lisa; Akbar, Akbar; Sakira, Hanni; Tampati, Riko; Yanti, Rina Trisna; Handayani, Tita; Susanti, Neri (Universitas Dehasen Bengkulu, 2025)
Plastic waste is a major environmental concern, especially when it is not properly managed. Uncontrolled plastic can pollute soil and water and negatively impact health and ecosystems. As a solution, students from KKNT UNIVED 2025 conducted socialization and demonstration activities in RT 33 RW 04, Pematang Gubernur Subdistrict, Bengkulu City, focusing on turning plastic waste into eco paving. The program aimed to raise awareness and provide skills for the community in waste processing. The methods included initial surveys, educational outreach and live demonstrations. The result revealed strong enthusiasm among participants and increased community capacity in creating valuable products from plastic waste.